Potential and prospects of biomass as a source of renewable energy in Pakistan - Ali, Asad; Ayub, Khurram Shahzad; Tahseen Sadiq, Muhammad; Tanveer, Muhammad; Naseer, Hamza; Nadeem, Zoha; Aamir, Hafiz Muhammad (Frontiers in Chemical Engineering, 2023)
In an agricultural country like Pakistan, producing affordable and clean energy can be a challenging task. However, Pakistan has the potential to utilize various biomass feedstocks to generate renewable energy and tackle climate change while promoting sustainable development. Wheat, rice, sugarcane, and corn are the four main crops that yield a significant amount of residue, totaling 112.1 million tons per year. These residues have the potential to produce 3050 kWh/ton of energy, which can meet 14% of the energy demand in Pakistan, equivalent to 9.85 TW, starting in 2022. Gasification technology is a versatile option that efficiently converts biomass into energy, while reducing negative environmental impacts. The current research explores the feasibility of generating clean energy from crop residues with low emissions, addressing the country's energy needs, and supporting policymakers in promoting the use of biomass for energy production